ECMO for Cardiac Rescue after Accidental Intravenous Mepivacaine Application. (27th August 2012) - Froehle, Michael; Haas, Nikolaus A.; Kirchner, Guenther; Kececioglu, Deniz; Sandica, Eugen
Abstract : Mepivacaine is a potent local anaesthetic and used for infiltration and regional anaesthesia in adults and pediatric patients. Intoxications with mepivacaine affect mainly the CNS and the cardiovascular system. We present a case of accidental intravenous mepivacaine application and intoxication of an infant resulting in seizure, broad complex bradyarrhythmia, arterial hypotension and finally cardiac arrest. The patient could be rescued by prolonged resuscitations and a rapid initiation of ECMO and survived without neurological damage. The management strategies of this rare complication including promising other treatment options with lipid emulsions are discussed.